1998
DOI: 10.1111/j.1532-5415.1998.tb01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Functioning, Well‐Being, and Health Perception in Late Middle‐Aged and Older People: Comparing the Effects of Depressive Symptoms and Chronic Medical Conditions

Abstract: The unique contribution of depressive symptoms in dysfunction, poor health perception, and well-being typically exceeds that of medical conditions because depressive symptoms combine a moderately large unique risk with a rather high prevalence. Results expand the MOS and WHO findings to the community-dwelling late middle-aged and older population and to additional outcomes as well. Results underscore the importance of detection and management of (comorbid) symptoms of depression in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
148
2
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(167 citation statements)
references
References 43 publications
14
148
2
3
Order By: Relevance
“…GLAS was a population-based prospective followup study of the psychological and social determinants of disease, functional disability, wellbeing and utilisation of care in older people [21,[23][24][25][26][27]. The primary objective of this study was to identify the psychosocial factors that influence the trajectory of QoL, independently or in interplay with diseaserelated factors.…”
Section: Methodsmentioning
confidence: 99%
“…GLAS was a population-based prospective followup study of the psychological and social determinants of disease, functional disability, wellbeing and utilisation of care in older people [21,[23][24][25][26][27]. The primary objective of this study was to identify the psychosocial factors that influence the trajectory of QoL, independently or in interplay with diseaserelated factors.…”
Section: Methodsmentioning
confidence: 99%
“…Even when physical health conditions are controlled, perceived health has been found to predict a variety of outcomes, including quality of life, service utilization, morbidity, and mortality [1,[3][4][5][6][7]. Due to the greater likelihood of health deterioration, the significance of perceived health among older populations is pronounced [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on potential predictors of perceived health have focused their attention on the individuals' mood or emotional state, particularly depressive symptoms [7,[11][12][13]. Individuals with greater levels of depressive symptoms are likely to rate their health as poorer, and this association is sustained even after controlling for the effects of objective health indicators [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the partners, this was respectively 57.1%, 25.8%, and 17.2%. On a list of chronic conditions (Ormel et al, 1998), the majority of the patients reported at least one co-morbidity (73.7%) and the majority of the partners (62.9%) also indicated a chronic condition. In both patients and partners, high blood pressure was the most frequently mentioned health condition (31.2% patients, 19% partners).…”
Section: Descriptivesmentioning
confidence: 99%